Hippocratic screening and subchronic oral toxicity assessments of the methanol extract of Vatairea macrocarpa heartwood in rodents - Jesus,Neyres Z. T. (2012)
Vatairea macrocarpa (Benth.) Ducke, Fabaceae, is popularly known as 'angelim'. Its heartwood macerate is used to treat inflammation, gastric ulcer, diabetes and infections. The oral acute and subchronic toxicity of the methanol extract of V. macrocarpa heartwood (MEVm) was evaluated. In the Hippocratic screening, a single administration of MEVm was given orally to mice at doses ranging from 100 to 5000 mg/kg. In the subchronic study, MEVm was given orally as a daily administration for thirty days to Wistar rats at doses of 20, 100 and 500 mg/kg. In Hippocrtaic screening, doses of MEVm up to 5000 mg/kg did not cause any relevant behavioral changes or deaths thus making it impossible to establish the LD50. In subchronic assay, body weight gains and food intake were significantly reduced at the last week of treatment with 20 and 500 mg/kg dose. Serum triacylglycerides, total proteins and γ-glutamyltransferase activity were significantly reduced, while alkaline phosphatase activity was elevated. In hematological parameters, MEVm increased the percentage of segmented neutrophils cells at the highest dose. All alterations observed were minor in nature and were not accompanied by any relevant clinical signs or any histopathological changes. In conclusion, the results demonstrate relative safety profile of MEVm in the experimental animals.